Cardiovascular diseases («Internal Medicine». Modul 2). Part 4: The executive task force for students of 5th course of medical faculty - Berezin, A. E.; Demidenko, O. V.; Vizir, V. A.; Березін, Олександр Євгенійович; Деміденко, Олександр Вікторович; Візір, Вадим Анатолійович (Запорізький державний медичний університет, 2018)
The executive task force is provided for students of 5th courses of medical faculties for helping to study of some topics in the fields of cardiovascular diseases incorporated into the discipline «Internal Medicine». There is the information about the most important topics regarding diagnosis of cardiac diseases.
Серцево-судинні захворювання («Внутрішня медицина». Модуль 2). Ч. 4